Specific immunotherapy with mugwort pollen allergoid reduce bradykinin release into the nasal fluid - Gawlik, Radoslaw; Grzanka, Alicja; Jawor, Barbara; Czecior, Eugeniusz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction: A pathomechanism of allergic rhinitis is complex. A neurogenic mechanism seems to play a significant role in this phenomenon. Aim: The evaluation of influence of specific immunotherapy of mugwort pollen allergic patients on the bradykinin concentration in the nasal lavage fluid. Material and methods : The study included 22 seasonal allergic rhinitis patients. Thirty persons with monovalent allergy to mugwort pollen, confirmed with skin prick tests and allergen-specific immunoglobulin E, underwent a 3-year-long allergen immunotherapy with the mugwort extract (Allergovit, Allergopharma, Germany). The control group was composed of 9 persons with polyvalent sensitivity to pollen, who were treated with pharmacotherapy. Before the allergen-specific immunotherapy (AIT) and in subsequent years before the pollen seasons, a provocation allergen test with the mugwort extract was performed, together with collection of nasal fluids, where bradykinin concentration was determined according to Proud method. Results : There were similar levels of bradykinin in both groups at baseline prior to therapy (AIT group: 584.0 ±87.2 vs. controls 606.3 ±106.5 pg/ml) and changes after allergen challenge 1112.4 ±334.8 vs. 1013.3 ±305.9 pg/ml as well. The bradykinin concentration in nasal lavage fluid after mugwort challenge in 1 year was lower in the AIT group (824.1 ±184.2 pg/ml vs. 1000.4 ±411.5 pg/l; p < 005) with a further significant decrease after the 2nd and 3rd year of specific immunotherapy. Significant reduction of symptoms and medications use was observed in hyposensitized patients. Conclusions : A decreased level of bradykinin as a result of AIT suggests that some of the symptomatic benefits of AIT may be related to the reduced release of bradykinin into nasal secretions. These values correlate with clinical improvement within the course of treatment.